PELAKSANAAN E-LITIGASI DALAM PENYELESAIAN PERKARA SENGKETA EKONOMI SYARIAH DI PENGADILAN AGAMA MAKASSAR - Dewi Puji Astuti; Suriyadi (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2023)
Abstract E-litigation is a trial that is conducted electronically in a way that minimizes the parties' meeting face-to-face and coming to the court office. The main problem of this research is how is the practice of sharia economic dispute proceedings in the Makassar religious court through E-litigation and to find out the provisions of the implementation of E-litigation in the settlement of sharia economic dispute cases at the Makassar religious court. This type of research is classified as normative-empirical research with the research approach used is a statutory approach and a case approach. The results of this study indicate that in the implementation of E-litigation against sharia economic dispute cases at the Makassar Religious Court, the practice is the same as in ordinary cases. But the difference between E-litigation and manual is that E-Litigation is filed by E-court. When the first trial was held, if both the plaintiff and the defendant were present, an amicable settlement was sought. If successful in seeking peace, the case will not be continued. Technically, the parties can briefly conduct a series of court proceedings in front of a computer. In Article 2 Paragraph 4 of Law Number 48 Year 2009 concerning judicial power, it is stated that the judiciary must be carried out in a simple, fast and low cost manner. Keywords: E-Court, E-Litigation, Sharia Economic Disputes